An Integrative Approach to Autophagy and Oxidative Stress Pathways for Clinical Prediction in Colorectal Cancer: A Narrative Review - Welly Hartono Ruslim; Himmi Marsiati; Nunung Ainur Rahmah; Wifanto Saditya Jeo (International Journal of Psychology and Health Science, 2026)
Colorectal cancer (CRC) remains one of the leading causes of cancer-related morbidity and mortality worldwide. Increasing evidence suggests that oxidative stress and autophagy are interconnected biological processes involved in tumor initiation, progression, therapeutic resistance, and patient survival. However, their combined role as an integrated prognostic biomarker panel has not been comprehensively reviewed. This narrative review aimed to summarize current evidence on the interaction between oxidative stress and autophagy pathways and to evaluate the clinical potential of their biomarkers for prognostic prediction in CRC. This review was based on peer-reviewed open access publications from major scientific databases between 2019 and 2025. Studies that have assessed oxidative stress biomarkers, such as 8-hydroxy-2′-deoxyguanosine (8-OHdG), 4-hydroxynonenal (4-HNE), nuclear factor erythroid 2-related factor 2 (NRF2), Kelch-like ECH-associated protein 1 (KEAP1), and autophagy-related biomarkers, including microtubule-associated protein 1 light chain 3 beta (LC3B) and sequestosome 1 (p62/SQSTM1) were critically synthesized. Current evidence suggests a role for oxidative stress and autophagy dysregulation in the development of CRC. Increased expression of LC3B, p62/SQSTM1, NRF2, and 8-OHdG is always associated with advanced disease, treatment resistance, tumor recurrence, and poor overall survival. Integrating biomarkers from both pathways appears to improve prognostic accuracy compared with individual biomarkers. Combined assessment of oxidative stress and autophagy biomarkers represents a promising prognostic approach for CRC. Nevertheless, large prospective studies are required to validate their clinical utility before routine implementation in precision oncology.